Computational Modeling for Hemodynamic Analysis of Stenosed Carotid Artery - Laiba Junaid; Natasha Mohsin Butt; Tayaba Naz; Arham Saddique; Syed Mudassir Hussain; Faisal Amin; Muhammad Abrar Baig (Sukkur IBA Journal of Emerging Technologies)
Atherosclerosis is the accumulation of lipids, cholesterol, and other substances inside and on the arterial walls known as plaque. Atherosclerosis can constrict the arteries and obstruct the blood flow. Additionally, the plaque may rupture the artery and clot blood. Blood flow patterns and hemodynamic parameters in the carotid artery have been widely associated with the onset and progression of atherosclerosis. Depending on the severity, stenosis in the arteries may lead to abnormal Blood flow conditions that can result in heart attack or stroke. A 2D model of the Carotid Artery has been studied representing Blood flow changes in the carotid artery along with the obstruction faced by Blood due to plaque which is formed by the deposition of fat and cholesterol on the side walls of the carotid artery. This study created a workflow for analysis utilizing a 2D model of the carotid artery with a total length of 60 mm and a diameter of 4.3 mm to estimate the carotid artery hemodynamics. COMSOL Multiphysics 6.0 has been used to construct and simulate the model of a blood vessel, along with the deposition of plaque, stenosis, sequential obstruction of outlets, and load application on it. The simulations showed that the lumped parameter model produces hemodynamic parameter values that are consistent with physiological reality. The simulation experiments demonstrate that hemispherical carotid artery blockages are extremely precarious and may be a factor in an impending ischemic stroke or cerebrovascular accident. The main goal is to evaluate scenarios reflecting changes in blood flow velocity and pressure, due to the narrowing of the artery, plaque formation, and the effect of closing any of its openings, between a healthy artery and an artery with disease.